Metabolic targeting, immunotherapy and radiation in locally advanced non-small cell lung cancer: Where do we go from here? - Dhawan, Annika; Pifer, Phillip M.; Sandulache, Vlad C.; Skinner, Heath D. (Frontiers in Oncology, 2022)
In the US, there are ~250,000 new lung cancer diagnoses and ~130,000 deaths per year, and worldwide there are an estimated 1.6 million deaths per year from this deadly disease. Lung cancer is the most common cause of cancer death worldwide, and it accounts for roughly a quarter of all cancer deaths in the US. Non-small cell lung cancer (NSCLC) represents 80-85% of these cases. Due to an enormous tobacco cessation effort, NSCLC rates in the US are decreasing, and the implementation of lung cancer screening guidelines and other programs have resulted in a higher percentage of patients presenting with potentially curable locoregional disease, instead of distant disease. Exciting developments in molecular targeted therapy and immunotherapy have resulted in dramatic improvement in patients’ survival, in combination with new surgical, pathological, radiographical, and radiation techniques. Concurrent platinum-based doublet chemoradiation therapy followed by immunotherapy has set the benchmark for survival in these patients. However, despite these advances, ~50% of patients diagnosed with locally advanced NSCLC (LA-NSCLC) survive long-term. In patients with local and/or locoregional disease, chemoradiation is a critical component of curative therapy. However, there remains a significant clinical gap in improving the efficacy of this combined therapy, and the development of non-overlapping treatment approaches to improve treatment outcomes is needed. One potential promising avenue of research is targeting cancer metabolism. In this review, we will initially provide a brief general overview of tumor metabolism as it relates to therapeutic targeting. We will then focus on the intersection of metabolism on both oxidative stress and anti-tumor immunity. This will be followed by discussion of both tumor- and patient-specific opportunities for metabolic targeting in NSCLC. We will then conclude with a discussion of additional agents currently in development that may be advantageous to combine with chemo-immuno-radiation in NSCLC.